Molecular Design of Novel Chemicals for Iron Sulfide Scale Removal - Abdulmujeeb T. Onawole; Ibnelwaleed A. Hussein; Hassan I. Nimir; Musa E. M. Ahmed; Mohammed A. Saad (Journal of Chemistry)
Scale deposition is a pertinent challenge in the oil and gas industry. Scales formed from iron sulfide are one of the troublous scales, particularly pyrite. Moreover, the use of biodegradable environmentally friendly chemicals reduces the cost compared to the conventional removal process. In this work, the chelating abilities of four novel chemicals, designed using the in silico technique of density functional theory (DFT), are studied as potential iron sulfide scale removers. Only one of the chemicals containing a hydroxamate functional group had a good chelating ability with Fe2+. The chelating strength and ecotoxicological properties of this chemical were compared to diethylenetriaminepentaacetic acid (DTPA), an already established iron sulfide scale remover. The new promising chemical surpassed DTPA in being a safer chemical and having a greater binding affinity to Fe2+ upon optimization, hence, a better choice. The presence of oxime (-NHOH) and carbonyl (C=O) moieties in the new chemical showed that the bidentate form of chelation is favored. Moreover, the presence of an intramolecular hydrogen bond enhanced its chelating ability.